Occurrence of Aggregatibacter actinomycetemcomitans in Indian chronic periodontitis patients and periodontally healthy adults - Vinayak Mahableshwar Joshi; Kishore Gajanan Bhat; Manohar Suresh Kugaji; Preeti Shivaji Ingalgi (Wolters Kluwer Medknow Publications, 2016)
Background: Aggregatibacter actinomycetemcomitans (Aa), an important primary periodontal pathogen, is known for its strong virulence characteristics that cause periodontal disease. We investigated Aa occurrence in Indian individuals using culture and 16 s rDNA polymerase chain reaction (PCR). Materials and Methods: A cross-sectional study with 100 participants each in the healthy and chronic periodontitis (CP) groups was conducted. The subgingival plaque was collected and immediately plated on selective media for Aa. The remaining plaque samples were used for DNA extraction. PCR was performed using specific primers for Aa. Statistical Analysis Used: The detection of bacteria and the clinical parameters between the groups were compared using the Mann-Whitney U-test. For assessing the agreement between the results of anaerobic culture and PCR, Kappa analyses were performed. Results: Aa levels using culture and PCR was 51% and 69% in the CP group and 12% and 30% in the healthy group, respectively. The two groups showed significant differences (P < 0.00001). The detection accuracy of culture and PCR was assessed, and the coefficient of accuracy (k) was highly significant in the healthy (0.3103; P < 0.0001) and CP groups (0.1536; P < 0.0497). Conclusions: Aa was predominantly found in the CP group compared with the healthy group, which is consistent with previous findings. Our results showed that both techniques can be used for detecting Aa. An ideal technique for detecting subgingival microorganisms should be carefully selected depending on the scope of the intended future work.